2019
DOI: 10.3390/su11123384
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of RC Structures by Using Engineered Cementitious Composites: A Review

Abstract: This paper presents a review of the recent work assessing the performance of building structures strengthened with engineered cementitious composite (ECC). ECC characterizes tensile strain hardening and multiple cracking properties, as well as strong interfacial bonding performance with substrate concrete, which makes it a promising retrofitting material. A lot of researches have been conducted on reinforced concrete (RC) structures, including beams, columns, beam–column joints, and fire-damaged slabs, strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Several studies have investigated the effectiveness of SHCC concrete hybrid systems for different structural members, for example shear strengthening by placing SHCC on sides of a beam [5,6] and flexural strengthening by placing SHCC at the tension side [7]. An overview of strengthening applications can be seen in [8]. These studies, along with the study on new hybrid system [9], demonstrate the promising application of hybrid structures by highlighting the increase in load-carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the effectiveness of SHCC concrete hybrid systems for different structural members, for example shear strengthening by placing SHCC on sides of a beam [5,6] and flexural strengthening by placing SHCC at the tension side [7]. An overview of strengthening applications can be seen in [8]. These studies, along with the study on new hybrid system [9], demonstrate the promising application of hybrid structures by highlighting the increase in load-carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, lateral load resistance and deformation capacity were improved as a result of the high tensile properties of the retrofitting material. In a state-of-the art review of strengthening applications with ECC, Shang et al 2019 [23] concluded that the strain-hardening property of ECC renders it an ideal retrofitting material; the interfacial resistance is adequate to ensure monolithic behavior between core and jacket, which is a finding that is also supported by inclined interface shear tests between plain and ECC concrete, particularly if the substrate is roughened prior to the strengthening application. It is also worth mentioning that the results of the present work are in line with the findings of Papavasileiou et al 2020 [24], who demonstrated that implementing a thin jacket layer to a deficient member is an effective retrofit technique that can be competitive to other strengthening methods (such as conventional thicker jackets or bracings at frame bays), provided that the thin jacket is composed of appropriate material(s) to develop sufficient confinement of the core and the additional strength required for the retrofitted member.…”
Section: Envelope Resistance Curvesmentioning
confidence: 99%
“…A new material Engineered Cementitious Composites (ECC) having many favourable properties such as damage tolerance, delamination resistance, etc. It has been found very effective in improving the interfacial bond performance with the substrate concrete [4]. Use of ECC in combination with high-strength polyethylene fibres to develop fibre RC jackets was examined [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several techniques for strengthening the existing buildings, such as enhancing the stiffness, improving discontinuity or irregularity in the distribution of stiffness of a building, have been examined and analysed in recent years. In the construction field, Reinforced Concrete (RC) is still the most widely used material being used [4]. Load bearing members such as beam and column largely utilises concrete and steel.…”
mentioning
confidence: 99%